PENGARUH SELF EFFICACY DAN WORK-LIFE BALANCE TERHADAP EMPLOYEE PERFORMANCE MELALUI MEDIASI EMPLOYEE ENGAGEMENT PADA YAYASAN HASAN KAFRAWI MAYONG - Alviana, Rizka Mala Dian; Imron, Much (LP2M Universitas Bina Bangsa, 2025)
This study is a quantitative research that aims to analyze the influence of self-efficacy and work-life balance on employee performance through employee engagement mediation at the Hasan Kafrawi Mayong Foundation. The method used was 120 employees and the sample was selected by the saturated sampling technique. The data was collected using questionnaires that had been tested for validity and reliability, and analyzed using Structural Equation Modeling (SEM) with Smart PLS 4 software. The results show that Self Efficacy and Work-Life Balance have a positive and significant influence on Employee Performance, with Employee Engagement as a mediating variable. These findings provide important insights for human resource development and performance improvement strategies in organizations